2003
DOI: 10.1023/a:1022624303979
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The oxidation of ammonia to nitrogen or nitric oxide, respectively, was investigated using on the one hand a pol ycrystalline copper foil and on the other hand deposited copper clusters prepared with the inert gas aggregation technique. The behavior in the ammonia oxidation of both model catalysts was studied using in situ near edge X-ray absorption fine structure (NE XAFS) spectroscopy in the soft X-ray range and mass spectrometry. It is shown that the copper foil reacts in a similar way as the copper cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…In the next step Mayer et al extended their studies for deposited copper clusters prepared with the inert gas aggregation technique. 127 It was reported that copper(I) nitride, which is responsible for deactivation of copper, was formed on both copper polycrystalline foil as well as copper clusters. Thus, it was assumed that the experiments and results obtained with copper foil as a model catalyst in ammonia oxidation was exemplary for the reaction behaviour of copper clusters or small particles.…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…In the next step Mayer et al extended their studies for deposited copper clusters prepared with the inert gas aggregation technique. 127 It was reported that copper(I) nitride, which is responsible for deactivation of copper, was formed on both copper polycrystalline foil as well as copper clusters. Thus, it was assumed that the experiments and results obtained with copper foil as a model catalyst in ammonia oxidation was exemplary for the reaction behaviour of copper clusters or small particles.…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…Further studies over peroxidised polycrystalline copper foil proved copper oxide as active phase for NH3-SCO [113,117]. However, due to unsatisfying selectivity to N2, further studies concerning ammonia oxidation over copper oxide supported e.g.…”
Section: Copper Oxidesmentioning
confidence: 98%
“…113,117] 33,126]. We summarized the catalytic performances of these catalysts (Table 2) as well as their physicochemical properties (Table 3).…”
Section: Copper Based Catalystsmentioning
confidence: 99%
“…In subsequent papers a similar method was employed for observation of the nitrogen K-edge through ammonia gas, but normalisation instead uses the sharp N-H * resonance from the gas phase ammonia to obtain the surface only contribution. 44,45 It was also noted that observation of the copper L-edge was not significantly effected by the gas phase and the surface copper spectrum could be retrieved from either the sample(I2/I0) or the collection plate(I3/I0). 44 The same setups have been used to record Fe Ledge spectra of Fe/ZSM-5 and the benefited from the much higher resolution of soft x-rays compared with hard x-rays along with the relatively large, systematic variation of the spectral features in the metal (Fe) L-edge with the oxidation state.…”
Section: Design Evolution and Limitation Of In Situ Cells For Soft Xas I: Berlinmentioning
confidence: 99%
“…As before polycrystalline copper foil had been used as a catalyst mimic, but a subsequent study shows that the same general structure-activity correlations (although at slightly lower temperature) could be seen for Cu particles (~ 2.8 nm), which were prepared on a carbon coated gold TEM grid using a gas aggregation technique. 45 It is of course fortuitous (or a good reaction choice) that the pressure range accessible with the soft XAS setup used (< few mbar) and the pressure range in which marked changes in reactivity were established (0.4 vs 1.2 mbar) were well aligned. For this series of papers, a clear question must be asked as to the effect of increasing the pressure again by a factor of ~10 3 to pressures of real world catalytic relevance.…”
Section: New Insights In Heterogonous Catalysis From Soft Xasmentioning
confidence: 99%